Psychometric Meta‐Analysis of the English Version of the Beck Anxiety Inventory. (9th June 2016) - Bardhoshi, Gerta; Duncan, Kelly; Erford, Bradley T.
Abstract : This meta‐analysis reviewed 192 scholarly works from 1993 to 2013 using the Beck Anxiety Inventory (Beck & Steer, 1993 ). Aggregated internal consistency (coefficient alpha) was .91 ( k = 117), and test–retest reliability was .65 ( k = 18). Convergent comparisons were robust across 33 different anxiety instruments and the Beck Depression Inventory–II (Beck, Steer, & Brown, 1996 ). Structural validity primarily supported the original 2‐factor solution proposed by Beck and Steer (1993 ), and diagnostic accuracy varied according to the sample size and criterion cutoff score.